2015
DOI: 10.1016/j.cmet.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1R Agonists Promote Normal and Neoplastic Intestinal Growth through Mechanisms Requiring Fgf7

Abstract: Glucagon-like peptide-1 (GLP-1) secreted from enteroendocrine L cells promotes nutrient disposal via the incretin effect. However, the majority of L cells are localized to the distal gut, suggesting additional biological roles for GLP-1. Here, we demonstrate that GLP-1 receptor (GLP-1R) signaling controls mucosal expansion of the small bowel (SB) and colon. These actions did not require the epidermal growth factor (EGF) or intestinal epithelial insulin-like growth factor (IGF1) receptors but were absent in Glp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
107
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 54 publications
13
107
2
Order By: Relevance
“…40 The effects of incretin therapy on colonic epithelia are not entirely clear: it was previously suggested that GLP-1RA and DPP4 inhibitors have the capacity to decrease growth and survival of colon cancer cells 74 ; however, more recent preclinical data indicate that GLP-1RA agonists may promote small and large bowel tumor growth. 41 Of interest, an increased risk of colorectal cancer has been reported after bariatric surgery, which has been proposed to be the result of increased incretin secretion. 75 As these incretin-based agents are increasingly used in the treatment of T2DM, their potential antineoplastic and procarcinogenic effects must be further addressed in clinical studies.…”
Section: Incretin-based Drugs and Cancermentioning
confidence: 99%
“…40 The effects of incretin therapy on colonic epithelia are not entirely clear: it was previously suggested that GLP-1RA and DPP4 inhibitors have the capacity to decrease growth and survival of colon cancer cells 74 ; however, more recent preclinical data indicate that GLP-1RA agonists may promote small and large bowel tumor growth. 41 Of interest, an increased risk of colorectal cancer has been reported after bariatric surgery, which has been proposed to be the result of increased incretin secretion. 75 As these incretin-based agents are increasingly used in the treatment of T2DM, their potential antineoplastic and procarcinogenic effects must be further addressed in clinical studies.…”
Section: Incretin-based Drugs and Cancermentioning
confidence: 99%
“…Indeed, we now understand that GLP-1 controls inflammation (75), reduces experimental kidney injury (76), and like GLP-2, acts as a potent intestinal growth factor through mechanisms including stimulation of crypt fission (ref. 77 and Figure 6). Among the actions of GLP-1 that have engendered the most interest are its effects in the cardiovascular system.…”
Section: Challenges In Studies Of Glp-1 and In Development Of Glp-1r mentioning
confidence: 99%
“…Long-term safety concerns related to the induction of tachycardia (GLP-1 receptor agonists only), a potential risk of pancreatitis, pancreatic cancer, thyroid cancer, colon cancer, cholecystitis and heart failure (in a trial with saxagliptin) have been expressed [4,16]. Nevertheless, data available at this point in time still indicate a favourable risk-benefit ratio.…”
Section: Incretin-based Therapies: Dealing With Safety Concernsmentioning
confidence: 99%